Size and density mediate transitions between competition and facilitation. (30th August 2019) - Cameron, Hayley; Coulson, Tim; Marshall, Dustin J.
Abstract: Species simultaneously compete with and facilitate one another. Size can mediate transitions along this competition–facilitation continuum, but the consequences for demography are unclear. We orthogonally manipulated the size of a focal species, and the size and density of a heterospecific neighbour, in the field using a model marine system. We then parameterised a size‐structured population model with our experimental data. We found that heterospecific size and density interactively altered the population dynamics of the focal species. Size determined whether heterospecifics facilitated (when small) or competed with (when large) the focal species, while density strengthened these interactions. Such size‐mediated interactions also altered the pace of the focal's life history. We provide the first demonstration that size and density mediate competition and facilitation from a population dynamical perspective. We suspect such effects are ubiquitous, but currently underappreciated. We reiterate classic cautions against inferences about competitive hierarchies made in the absence of size‐specific data.